(untitled) (SCIENCE TIME JOURNAL, 2026)
This article explores the discursive function of metafiction in David Lodge’s Changing Places: A Tale of Two Campuses. The study investigates how metafictional discourse transforms the academic novel into a self-conscious narrative structure that simultaneously satirizes university culture and reflects upon the processes of literary representation. Drawing upon narratology, discourse analysis, and postmodern literary theory, the research examines narrator intervention, epistolary structure, metalinguistic commentary, and genre self-awareness as major metafictional devices. Particular attention is devoted to how the novel foregrounds its own fictionality and challenges conventional distinctions between reality and representation. The findings demonstrate that metafiction in Changing Places serves both aesthetic and ideological functions: it destabilizes narrative authority, critiques academic discourse, and encourages readers to participate in interpretation actively. The article concludes that Lodge transforms the campus novel into a postmodern narrative experiment in which storytelling itself becomes the subject of analysis.